Philosophy and religious architecture. The memory of the catholic worship building - Mariana Melisa Costante (ARQUISUR Revista, 2023)
This reflective work arises from the conviction that the fundamental object of the ecclesiastical building of Catholic worship goes further beyond the limits of serving as support for the liturgical program. From the common ground of the profane, its essential task lies in the sensible concretion of a fundamental ‘vision’ of existence (God–I–world). Based on the philosophical trends that characterize the interaction of the immanent and the transcendent, this work is intended to enrich the most opportune paths of thought and action for the effective resolution of the religious program, contemplating its anchorage in the secular world without retracting its ‘sacred’ character. To this end, after inquiring into the primitive nature of these enclosures and their resignification over the past century −attending in parallel to metaphysical and epistemological transformations of contemporary culture− their current production will be explored through five small chapels, granting special interest to their aesthetic and symbolic qualification. This journey will enable the construction of a particular frame for the general outlook of this architecture to identify new modes of representation of the sacred in which the ‘architectural materiality’ prevails as a resource for updating the cultic memory.